Knowledge Regarding Blood Pressure Measurement among First and Second Year Undergraduate Medical Students: A Descriptive Cross-sectional Study - Shavana Rajya Laxmi Rana; Bikalp Thapa; Lee Budhathoki; Yesha Shree Rajaure; Bipin Kumar Shrestha; Barun Mahat; Sunil Dhungel; Tara Man Amatya (Journal of Nepal Medical Association, 2022)
Introduction: Blood pressure measurement has a great implication in medicine. Every medical personnel should have a sound knowledge regarding blood pressure measurement. This study was conducted with the aim of determining the knowledge regarding blood pressure measurement among first and second year medical students of a medical college.